Cerebral protection in left atrial appendage closure in the presence of appendage thrombosis. Issue 3 (18th August 2020) - Boccuzzi, Giacomo G.; Montabone, Andrea; D'Ascenzo, Fabrizio; Colombo, Francesco; Ugo, Fabrizio; Muraglia, Simone; De Backer, Ole; Nombela‐Franco, Luis; Meincke, Felix; Mazzone, Patrizio
Abstract: Background: Presence of thrombus in the left atrial appendage (LAA) remains a severe contraindication to the percutaneous left atrial appendage closure procedure (LAAC), due to increased embolic risk. Recently, the experience developed in cerebral protection device in transcatheter aortic valve implantation (TAVI) procedure was translated in LAAC to address this issue. Aim: To evaluate efficacy and safety of Sentinel cerebral protection system (CPS) in supporting LAAC in real‐world patient with persistent LAA thrombus. Methods and results: The study retrospectively enrolled consecutive patients with non‐valvular atrial fibrillation (NVAF) and thrombus in LAA who underwent LAAC supported by Sentinel CPS in seven European high‐volume centres. Twenty‐seven patients were included with a median age of 69.1 ± 9.7 years old, with median CHA2 DS2 ‐VASc and HAS‐BLEED scores 3 [2–5] and 3 [2.75–4], respectively. Technical and procedural success was achieved in all patients. No periprocedural TIA, stroke, or supra‐aortic trunks dissection was recorded. Conclusions: In this multicenter registry, LAAC supported by Sentinel CPS in patients with LAA persistent thrombus seems to be a safe and efficacious treatment.